2004
DOI: 10.1051/0004-6361:20031578
|View full text |Cite
|
Sign up to set email alerts
|

The age of the oldest Open Clusters

Abstract: Abstract. We determine ages of 71 old Open Clusters by a two-step method: we use main-squence fitting to 10 selected clusters, in order to obtain their distances, and derive their ages from comparison with our own isochrones used before for Globular Clusters. We then calibrate the morphological age indicator δ(V), which can be obtained for all remaining clusters, in terms of age and metallicity. Particular care is taken to ensure consistency in the whole procedure. The resulting Open Cluster ages connect well … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
261
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(304 citation statements)
references
References 36 publications
36
261
7
Order By: Relevance
“…13 also shows little correlation. Carraro et al (1998), Chen et al (2003, and Salaris et al (2004) also did not find any relation between the ages and metallicities for their OCs. The significant scatter in the ages and metallicities dominates and hides any possible small correlation.…”
Section: Comparisons Of Morphological and Isochrone Agesmentioning
confidence: 88%
See 1 more Smart Citation
“…13 also shows little correlation. Carraro et al (1998), Chen et al (2003, and Salaris et al (2004) also did not find any relation between the ages and metallicities for their OCs. The significant scatter in the ages and metallicities dominates and hides any possible small correlation.…”
Section: Comparisons Of Morphological and Isochrone Agesmentioning
confidence: 88%
“…The morphological ages are estimated from the equation, logA = 0.04δV 2 + 0.34δV + 0.07[F e/H] + 8.76 of Salaris et al (2004), applying the metal abundances, [Fe/H], of the OCs in Table 6. These ages of 12 OCs together with their uncertainties have been listed in Column 8 of Table 9.…”
Section: Comparisons Of Morphological and Isochrone Agesmentioning
confidence: 99%
“…According to Salaris et al (1993), as long as the α-elements have approximately the same enhancement, scaled-solar models mimic α-enhanced models computed with the same global metallicity [M/H]. This is, however, strictly true only for [M/H] values up to ∼-1.0, as shown by Salaris & Weiss (1998) and Vandenberg et al (2000). For higher global metallicities this equivalence is not well satisfied anymore.…”
Section: The Theoretical Frameworkmentioning
confidence: 94%
“…Therefore we investigated how different would be the ∆F555W bump HB parameter at a given [M/H] larger than −1, for a scaled-solar and an α-enhanced metal mixture. We used isochrones by Salaris & Weiss (1998) with [M/H] = −0.3 (approximately the upper end of the metallicity range spanned by our GGC sample), both scaled-solar and with [α/Fe] = 0.4; we found that the ∆F555W bump HB values are changed by only 0.05 mag for typical GGC ages, the α-enhanced ones being larger. This is however just an upper limit to the real difference, since these metal rich clusters seem to show an α-enhancement lower than [α/Fe] = 0.4.…”
Section: The Theoretical Frameworkmentioning
confidence: 99%
“…As for the estimates of the absolute age of NGC 362, they range from 8.7 Gyr (Salaris & Weiss 1998) and 9.9 Gyr (Carretta et al 2000) to 11-12 Gyr (Vandenberg 2000). Since the differences of Hβ, Mg 2 , Mgb, and Fe indices between NGC 362 and GC in DDO 78…”
Section: Globular Cluster Metallicity and Agementioning
confidence: 99%